APLIKASI PEMBELAJARAN ILMU BIBLIOMATRIKS DI PERGURUAN TINGGI - Tri Margono, Tri Margono (Jurnal Cakrawala Pendidikan, 2016)
Experts in use Inethodology for analyzing their research especialy in the. of information sciens often have differences, athough they ae more use case studies in the fact. The studies describe diferent yield, cause the affect ofth yield more depend on the various of problems on the specific case and ols that used by expel1 in count to the analyzing yield. The etlort toovercome the d’ifferences should interceded in oder to obtain prctice in application the problem .is using bibliomatrics method. The expert seldom use the method in practice work, acually the method more important in research planning. Also can use to develop of nw subject heading on interdisciplnary publication that publilished during many yeas ago. ’l’roughthe method every difficulty could exceed, so the .information maagement in developing the classification of information obtained by expert base on right structure from interdisciplinary. The impotant of the effort fOI" information organizing and easy to use it in proce sing of right documents indentification as suitable with’ user’s needs could be done by bibliomatrics. Bibliomatrics could use as tool detect core problems to obtain the collection development. Teaching l11ethod of biblioillatries at univerities could develop through seminar activity, whwere the ield iJnplemented with other .methods,.. also through using, online system as base for developig· of the nlethod itself.